Geological interpretation of a seismic reflection profile in the eastern part of the Bohemian Cretaceous Basin - Skacelova,Z.; Mlcoch,B.; Cech,S. (Journal of Geosciences, 2022)
A seismic reflection profile was realized in the eastern part of the Bohemian Cretaceous Basin in the years 2013-2015. Seismic research was supported by a detailed gravity and geoelectric survey. The profile crossed three significant hydrogeological structures or districts: Vysoke Myto, Usti and Kysperk synclines. Interpretation of geophysical data enabled a determination of the Cretaceous sediments with a thickness of up to 250 m and Permian sediments even with a thickness of 2000 m. The seismic reflectors and gravity effect, together with the boreholes and geological mapping, were used to compile the uncovered geological map.
Keywords: Bohemian Cretaceous Basin; reflection seismic; gravity; basement; tectonics; hydrogeological structures